Comparison of Metoprolol and Sacubitril/Valsartan in Chinese Patients With Heart Failure: A Retrospective Cohort Study - Yali Huang; Qianni Lan; Yuan Liu (Dose-Response)
Background Sacubitril/valsartan is recommended for patients with New York Heart Association class II to III heart failure (class 1 recommendation). The objectives of the study were to evaluate the effectiveness and safety of metoprolol against sacubitril/valsartan in patients with heart failure and reduced ejection fraction (HFrEF). Methods In retrospective study, patients aged ≥18 years with heart failure and less than 40% of left ventricular ejection fraction received 25 mg metoprolol once daily (ML cohort, n = 117) or 50 mg sacubitril/valsartan twice daily (SV cohort, n = 128) for 6-months. Results Systolic and diastolic blood pressures, heart rates, N-terminal pro-brain natriuretic peptide values, and left ventricular ejection fraction values improved across both cohorts, especially in the ML cohort after treatments for 6-months as compared to before treatments ( P < .05 for all). Death was higher in the SV cohort than in the ML cohort over 15 months (10 (8%) vs. 2 (2%), P = .0362). Fatigue, depression, shortness of breath, and wheezing have been reported in patients in the ML cohort. Dizziness, hyperkalemia, fatigue, abdominal or stomach pain, and blurred vision have been reported in patients in the SV cohort. Conclusions Metoprolol may offer superior safety with comparable efficacy.